Single nucleotide polymorphism of candidate genes in non-descript local goats of Sri Lanka - ARIYARATHNE, H B P C; ARIYARATNE, H B S; LOKUGALAPPATTI, L G S (The Indian Journal of Animal Sciences, 2017)
In the present study, genetic polymorphism in exon 4 of kappa casein (k-CSN3), exon 2-3 of alpha lactalbumin (LALBA) and exon 1 of gonadotropin releasing hormone receptor (GnRHR) genes were analyzed as candidate genes for milk production, milk quality and prolificacy in non-descriptive local goats in Sri Lanka. Altogether eleven, one and three single nucleotide polymorphisms (SNPs) were identified in k-CSN3, LALBA and GnRHR gene fragments, respectively utilizing the DNA sequencing technique for the first time in Sri Lanka. Seven polymorphic sites out of eleven in k-CSN3 gene fragment and the recorded variable site in LALBA gene fragment were homozygous while all three polymorphic sites in GnRHR gene fragment were heterozygous. Two of the SNPs recorded in the present study are known to be unique for Sri Lankan non-descript goat population at G203T and A730G in k-CSN3 and GnRHR genes, respectively. The study records another two SNPs in GnRHR gene, which are already known to be correlated with higher fecundity in goats (G757A and G891T). Results of the present study will be extremely important in future attempts to develop markers to improve the milk production, milk composition and litter size of non-descript local goats in Sri Lanka.